Pengaruh Kualitas Layanan, Kepuasan Pelanggan dan Keterikatan Pelanggan terhadap Loyalitas Pelanggan Grab di Surabaya - Fadela Bara; Tjahjani Prawitowati (STIE Perbanas Surabaya, 2020)
Customer Loyalty indirectly help companies to promote products or services to the people closest to them. This is will be greatly help the company to get new customers. To increase Customer Loyalty, the company is expected to improve the quality of services provided. Quality is closely related to Customer Satisfaction and Customer Engagement, quality encourages customers to establish long-term bonds of mutual benefit in the company and Customer Engagement can increase Customer Loyalty because of the high level of Customer Engagement is the result of Customer Satisfaction of the product or service provided by the company.